The effects of oleuropein on apoptotic rate and oxidative stress profiles during tumour promotion stage in the mouse skin carcinogenesis model - Siti Fathiah Masre; Azim Izzuddeen; Dayang Noor Suzliana John; Zariyantey Abdul Hamid (Penerbit Universiti Kebangsaan Malaysia, 2019)
Oleuropein is a phenolic compound that can be abundantly found in the olive plant and it possesses pharmacological properties including anticancer, antioxidant, and anti-inflammatory. This present study was designed to determine the effects of oleuropein on tumour promotion stage, particularly on the histopathological changes, apoptotic rates and oxidative stress profiles by using the mouse skin carcinogenesis model. Female ICR mice were randomly divided into 3 groups (n= 8 mice per group) as follows: Control induced with DMBA/TPA, negative control (acetone) and oleuropein-treated groups. For the treatment group, the mice were initiated with DMBA (200 nmol) followed by pre-treatment with oleuropein (10 mg/kg) and subsequent promotion with TPA (20 nmol). The treatments were topically applied on the shaved dorsal up to 10 weeks. Histopathology analysis showed that oleuropein-pretreated group appeared lack of thickness in epidermal hyperplasia, as compared to thick hyperplasia and epidermal disorganisation in the DMBA/TPA control group. Data also showed that oleuropein pre-treatment resulted in a significant increase of the apoptotic rates (p<0.05) as indicated by the activated caspase-3 labelling compared to DMBA/TPA group. Interestingly, the level of MDA is significantly reduced (p<0.05) in the oleuropein pre-treated group compared to DMBA/TPA group. Next, pre-treatment of oleuropein caused a significant decrease in the GSH levels (p<0.05) along with a significant increase in the SOD levels (p<0.05) compared to the DMBA/TPA group. Overall, this study indicates that oleuropein may act as a potential chemopreventive agent through its apoptotic and antioxidant defence activities on tumour promotion stage in skin carcinogenesis event.